Emergence and Rapid Spread of Carbapenem Resistance during a Large and Sustained Hospital Outbreak of Multiresistant Acinetobacter baumannii - Corbella, Xavier (American Society for Microbiology, 2000)
Beginning in 1992, a sustained outbreak of multiresistant Acinetobacter baumannii infections was noted in our 1,000-bed hospital in Barcelona, Spain, resulting in considerable overuse of imipenem, to which the organisms were uniformly susceptible. In January 1997, carbapenem-resistant (CR) A. baumannii strains emerged and rapidly disseminated in the intensive care units (ICUs), prompting us to conduct a prospective investigation. It was an 18-month longitudinal intervention study aimed at the identification of the clinical and microbiological epidemiology of the outbreak and its response to a multicomponent infection control strategy. From January 1997 to June 1998, clinical samples from 153 (8%) of 1,836 consecutive ICU patients were found to contain CR A. baumannii. Isolates were verified to be A. baumannii by restriction analysis of the 16S-23S ribosomal genes and the intergenic spacer region. Molecular typing by repetitive extragenic palindromic sequence-based PCR and pulsed-field gel electrophoresis showed that the emergence of carbapenem resistance was not by the selection of resistant mutants but was by the introduction of two new epidemic clones that were different from those responsible for the endemic. Multivariate regression analysis selected those patients with previous carriage of CR A. baumannii (relative risk [RR], 35.3; 95% confidence interval [CI], 7.2 to 173.1), those patients who had previously received therapy with carbapenems (RR, 4.6; 95% CI, 1.3 to 15.6), or those who were admitted into a ward with a high density of patients infected with CR A. baumannii (RR, 1.7; 95% CI, 1.2 to 2.5) to be at a significantly greater risk for the development of clinical colonization or infection with CR A. baumannii strains. In accordance, a combined infection control strategy was designed and implemented, including the sequential closure of all ICUs for decontamination, strict compliance with cross-transmission prevention protocols, and a program that restricted the use of carbapenem. Subsequently, a sharp reduction in the incidence rates of infection or colonization with A. baumannii, whether resistant or susceptible to carbapenems, was shown, although an alarming dominance of the carbapenem-resistant clones was shown at the end of the study.